Global complexity bound of the Levenberg–Marquardt method. (3rd July 2016) - Zhao, Ruixue; Fan, Jinyan
Abstract : In this paper, we propose a new updating rule of the Levenberg–Marquardt (LM) parameter for the LM method for nonlinear equations. We show that the global complexity bound of the new LM algorithm is, that is, it requires at most iterations to derive the norm of the gradient of the merit function below the desired accuracy .